The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1001/archpedi.156.3.252
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage in Children Younger Than 3 Years

Abstract: Computed tomographic imaging patterns of intracranial hemorrhage in children younger than 3 years help predict whether the injury was intentional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 14 publications
0
29
0
1
Order By: Relevance
“…Articles were included if they indicated the frequency of males and females with TBII and were classified into 3 TBII groups: Group 1-neonatal SDH from birth trauma 5,16 -21 Group 2-SDH in young infants from accidental falls [21][22][23][24][25][26][27][28][29][30][31][32] Group 3-SDH from nonaccidental TBII (SBS). 21,22,[27][28][29][30][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] The same type of literature search was also done to determine if there are any gender differences in macrocephaly related to IEAFS (also called external hydrocephalus, benign subdural collections of infancy, benign subdural hygromas, and other terms) which is group 4. If there was no association of gender with TBII or with macrocephaly, then the expected percentage of males would be about 51.4% which is the percentage of births that are male in North America and Europe over the second half of the 20th century.…”
Section: Methodsmentioning
confidence: 99%
“…Articles were included if they indicated the frequency of males and females with TBII and were classified into 3 TBII groups: Group 1-neonatal SDH from birth trauma 5,16 -21 Group 2-SDH in young infants from accidental falls [21][22][23][24][25][26][27][28][29][30][31][32] Group 3-SDH from nonaccidental TBII (SBS). 21,22,[27][28][29][30][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] The same type of literature search was also done to determine if there are any gender differences in macrocephaly related to IEAFS (also called external hydrocephalus, benign subdural collections of infancy, benign subdural hygromas, and other terms) which is group 4. If there was no association of gender with TBII or with macrocephaly, then the expected percentage of males would be about 51.4% which is the percentage of births that are male in North America and Europe over the second half of the 20th century.…”
Section: Methodsmentioning
confidence: 99%
“…The appearances of a SDH in the acute setting can range from homogenous hyper-, hypo-or mixed density, in patterns which may be laminated, layered or sedimented. Low or mixed density subdural collections may develop within the first 24 hours after head injury (Wells et al 2002;Vinchon et al 2003Vinchon et al , 2004Wells and Sty 2003;Zouros et al 2004). The acute low density fluid in isolation or in association with acute SDH may be because actively bleeding unclotted blood (hypodense) is mixing with clotted hyperdense blood, or because there is Widened subdural spaces (particularly in the frontal region) and a small persistent high signal of a posterior fossa subdural are seen.…”
Section: Subdural Haemorrhage and Brain Injuriesmentioning
confidence: 99%
“…The authors deemed all studies identified to have some methodological or quality issues as defined by a priori criteria. Four studies were specific to head injury, while three evaluated general abusive injuries [11][12][13][14][15][16][17]. The studies looked at a variety of predictive factors for child abuse including individual criteria such as severe retinal hemorrhage, brain ischemia, presence of subdural hematoma, lack of history or low-impact trauma history, imaging patterns, bruise location consistent with fracture site, as well as tools integrating multiple factors such as a combination of bruise region, age of child, and mechanism history or a combination of age of child, physical exam findings, and imaging results.…”
Section: Detection Of Child Abusementioning
confidence: 99%